Performance of masonry blocks incorporating Palm Oil Fuel Ash - Agus Setyo Muntohar, Muhammad Ekhlasur Rahman, dkk (ELSEVIER, 2014)
This paper presents an experimental study on the development of masonry block with Palm Oil Fuel Ash (POFA) as a partial replacement to cement whilst maintaining satisfactory properties of masonry block. The dosages of POFA are limited to 0%, 20%, 40% and 60% by mass of the total cementitious material in the masonry block. The experiments on masonry block investigate the compressive strength and the breaking load for mechanical properties and water absorption and efflorescence for its durability. The compressive strength and the breaking load of the masonry blocks reduce with increasing percentage of POFA replacement. However, it satisfies the requirements of Class 1 and Class 2 load-bearing masonry block according to Malaysian Standard MS76:1972. In terms of durability of the masonry block, water absorption for all the masonry blocks satisfies the requirement of ASTM C55-11 and there is no any sign of efflorescence on all the masonry blocks. POFA based masonry block are also found to be cheaper than the cement sand masonry blocks. The experimental studies indicate that POFA based masonry block has a significant potential for application in the construction industry.